Integration of Local Wisdom and Legal Certainty in the Development of Tourism Villages in Malang Regency - Azna Abrory Wardana (Institut Penelitian dan Pengembangan Mandalika Indonesia, 2025)
The development of tourism villages in Malang Regency has great potential in supporting the economy of local communities and preserving cultural and environmental wealth. Malang District, with its diversity of tourist villages rich in unique local wisdom and natural distinctiveness, requires an approach that integrates local wisdom and legal certainty to achieve sustainable tourism. Local wisdom includes cultural values, traditions, and social practices that have long been passed down and become a strong identity of each village, making it an important asset in attracting tourists through authentic experiences that are different from other destinations. This research analyzes how the integration of local wisdom and the support of legal certainty can create a safe, comfortable, and friendly tourism environment for visitors and local communities. Legal certainty through clear and structured regulations such as Law No. 10/2009 on Tourism and Regional Regulation of East Java Province No. 4 of 2022, is needed to provide protection of community rights and avoid conflicts in tourism management. The results of this study are expected to serve as a model for the development of tourism villages that not only focus on economic improvement, but also pay attention to cultural preservation, environmental sustainability, and local community empowerment. This integration creates a solid foundation for tourism villages in Malang Regency to develop sustainably and competitively in the long term.